Final answer:
To solve for r in terms of q, s, t, and u from the equation St = -ruq, divide both sides by -uq to isolate r, yielding the solution r = St / (-uq).
Step-by-step explanation:
The student has asked to solve for r in terms of q, s, t, and u from the equation St = -ruq. To solve for r, we need to manipulate this equation algebraically and isolate r on one side.
First, we divide both sides of the equation by -uq to get:
r = St / (-uq)
So, the solution for r in terms of q, s, t, and u from the equation St = -ruq is r = St / (-uq).